Wire length of midimew-connected mesh network - Awal, Md. Rabiul; Rahman, M.M. Hafizur; Mohd. Nor, Rizal; Tengku Sembok, Tengku Mohd; Miura, Yasuyuki; Inoguchi, Yasushi (Springer International Publishing, 2014)
Midimew connected Mesh Network (MMN) is a Minimal DIstance MEsh with Wrap-around links (midimew) network. In this paper, we present the architecture of MMN and evaluate the total wire length of MMN, TESH, mesh, and torus networks. It is shown that the proposed MMN possesses simple structure and moderate wire length. The total wire length of MMN is slightly higher than that of mesh network and lower than that of 2-D torus network. Overall performance suggests that, MMN is an optimal network among these networks.